Moluska di Pulau Kabaena, Muna, dan Buton, Sulawesi Tenggara - Hendrik A.W. Cappenberg, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Molluscs in Kabaena, Muna, and Buton Islands, Southeast Sulawesi. Kabaena, Muna, and Buton islands in Southeast Sulawesi waters have quite wide reef flats and rich in marine life, including molluscs. To determine the condition of mollusc communities in these waters, a study was conducted in May 2006 in five locations, namely Kabaena Island (2 stations), Muna Island (1 station), and the Buton Island (2 stations). The method used was transect squares starting from the beachfront perpendicular to the direction of the sea (the edge). From this study, 74 species of molluscs were obtained that consisted of 49 species of the class Gastropoda and 25 species of the class Bivalvia. Polinices tumidus, Engina alveolata, Vexillum sp., and Morula margariticola of the class Gastropoda and Gafrarium tumidum, Tellina sp.1, and Barbatia decussata of the class Bivalvia were molluscs that had a relatively large distribution. The highest mollusc density was found in Kalimbungu Bay (19.2 individuals/m2) and the lowest was in Lakeba (3.5 individuals/m2). Haelicus variegatus was a species that dominated the sand substrate in Kalimbungu Bay. The molluscs found in this study were common species in tropical waters. The value of species diversity index (H') ranged from 1.54 to 2.88. This value indicated the diversity of mollusc species was of moderate condition. Evenness index (J') ranged from 0.56 to 0.92 and dominance index (C) ranged from 0.08 to 0.40. Both values showed that the mollusc community in each study site was in a pretty good condition